Combined effects of antibiotics and acidified nitrite on biofilm formation by beta-lactamase-producing uropathogenic bacteria - Hassan, Hozan Yousif; Hanna Aka, Safaa Toma; Najmaddin Hamad , Aras; Jalal Balaky, Salah Tofik (Zanco Journal of Medical Sciences (ZJMS), 2023)
Background and objective: The increased prevalence of extended- spectrum beta-lactamase producing Enterobacteriaceae has increased the use of last-resort antimicrobial drugs like Carbapenems. An alternative idea is to use new combinations of common antibiotics. The aim of the present study is to examine whether acidified nitrite has the ability to enhance the activity of beta-lactam antibiotics against the biofilm formation and bacterial growth of beta-lactamase- producing uropathogenic isolates. Methods: In this cross-sectional study, a total of 37 beta-lactamase- producing uropathogens were collected from patients at Urology Department at Rizgary Teaching Hospital in Erbil/Iraq. Biofilm formation was determined using a 96-well tissue culture plate assay. The ability to produce beta-lactamase production was detected by a phenotypic confirmatory combination disk diffusion test. The sub-minimal inhibitory concentration of antibiotics alone and in combination with each of acidified nitrite, ascorbic acid and sodium nitrite towards biofilm formation were observed. Results: The combination of cefotaxime with each of acidified nitrite (P <0.001), ascorbic acid (P <0.001) and sodium nitrite (P = 0.003) significantly enhanced the effect of cefotaxime against the biofilm producing activity of beta-lactamase producing uropathogens. Furthermore, with ceftazidime identical synergistic results were obtained with ascorbic acid (P = 0.001) and acidified nitrite (P = 0.007). Conclusion: Acidified nitrite significantly improved the activity of beta-lactam antibiotics against the biofilm mass of beta-lactamase producing uropathogens.